Perancangan Sistem Informasi Manajemen Rumah Sakit Modul Sarana Dan Prasarana - Istri Alit Dwi Purnamaningrat, A.A.; Sukarsa, I Made; Ika Marini Mandenni, Ni Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.2 Agustus 2015, 2015)
Information about infrastructure in hospitals must be accurate, complete and relevant, but the current system  has not been optimally obtained. Now system in hospitals still use the conventional system . Conventional system was the process of storing data manually . These conventional systems make difficulties for employees to create reports, patients and visitors in search of information about the facilities and infrastructure was available at the  Hospital. System Information Infrastructures designed to help in the process of providing information that was easier for employees, patients and visitors as well as assist in the reporting process. Stages of making the system design was conducted using TAS (Total Architecture syntesis), they are determination of initial scope, determination of needs, determination of business processes, system design and evaluation. Infrastructures module has a recording process of master data, inventory management processes, management cleaning room, the asset management and reporting processes. This design can be used as a guide for programmers in the manufacture of Hospital Information System Integrated.
Keywords: Sistem Informasi, Sistem Informasi Manajemen Rumah Sakit, Sistem Informasi Sarana dan Prasarana, Total Architecture Syntesis